PENGEMBANGAN SISTIM PENDUKUNG KEPUTUSAN UNTUK MENDUKUNG PENGELOLAAN JARINGAN IRIGASI (Studi Kasus: Daerah Irigasi Batujai, Daerah Irigasi Mujur II, dan Daerah Irigasi Surabaya di Lombok Tengah ) - , Irwansyah ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In order to carry out the arrangement bureaucracy more effective and efficient, the government established a decentralized system that start with Act No. 5 of 1974 and then changed again into Law No. 22 of 1999 on Regional Government, in relation to governance also formed Government Regulation No. 25 of 2000 on the authority of provinces as autonomous region as well as Government Regulation No. 84 of 2000 on Guidelines for Organization of the Region. It turns out a variety of these regulations has not been able to create more effective and efficient bureaucracy, it appears evident from various short comings and multiple interpretations when these regulations are set. The the Government Regulation was changed to Government Regulation No. 8 of 2003 is expected to improve the exiting deficiencies in the previous regulations. However, when applied to such problems also arise sweeling number of regional organizations. For institutional aspects later replaced by Act No. 32 of 2004 on Regional Government which are presented in that Regulation No. 41 of 2007 for structuring regional organizations, with the established of this regulation expected to create an effective and efficient bureaucracy. This paper evaluates the implementation of Government Regulation No. 41 of 2007, especially in the city of Yogyakarta